Fund Directive Raises Big Workload Specter (Compliance Reporter, 2009)
A number of industry professionals are weighing the work that will flow from complying with the European Commission's proposed Alternative Investment Fund Managers Directive, which would subject hedge funds and other entities to higher standards on risks, liquidity and conflicts of interest. Many in the industry are holding fire on compliance plans, pending a final version of the Directive being passed. Tim Cornick, partner at Macfarlanes, said C/Os at FSA-registered hedge fund firms would have to start getting involved in continuing monitoring of both regulatory capital, as well as the limits on leverage. Other new tasks would include reporting to investors and regulators, such as on controlling influence functions in investee companies.